RESPON PERTUMBUHAN BIBIT TANAMAN SALAK PONDOH (Salacca edulis Reinw) AKIBAT BERBAGAI DOSIS PUPUK KANDANG AYAM - Josina Irene Brigetha Hutubessy; Konstantinus Febryanto Beda (AGRICA, 2019)
This study aims to know to employ organic fertilizer stall chicken at variable growth seed malacca with dose optimum organic fertilizer stall chicken the supply growth seed malacca the optimum. his study used a randomized block design (RAK) with treatment the at use PO0 = 0 gram polybag-1, PO1= 50 gram polybag-1 PO2 = 100 gram polybag-1, PO3 = 150 gram polybag-1, PO4 = 200 gram polybag-1. Variable growth observed in this study is plant height, wide of the leaf, the number of leaves, length of root, fresh of weight, and dry of weight. Data were statistically analyzed, and followed by test BNT standard 5 %. Studies indicate that present organic fertilizer stall chicken about malacca gives very real about all variable monitoring plant height 14,15%, wide of leaf 36,46%, the number of leaf 30,43%, long of root 21,00%, fresh of weight 47,42%, and dry of weight 42,44%. Dose optimum organic fertilizer stall chicken the supply growth seed malacca the optimum is 200 gram polybag-1.